2008
DOI: 10.1086/591493
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular Transport of Energetic Charged Particles in Nonaxisymmetric Two‐Component Magnetic Turbulence

Abstract: Q1,Q2 We examine energetic charged particle diffusion perpendicular to a mean magnetic field B 0 due to turbulent fluctuations in a plasma, relaxing the common assumption of axisymmetry around B 0 and varying the ratio of two fluctuation components, a slab component with parallel wavenumbers and a two-dimensional (2D) component with perpendicular wavenumbers. We perform computer simulations mostly for 80% 2D and 20% slab energy and a fluctuation amplitude on the order of B 0. The nonlinear guiding center (NLGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Previous computer simulations have shown that in some cases, corresponding to Regime 3 above, temporary topological trapping and suppressed diffusive escape apply to subsets of field lines (with "conditional statistics" that depend on the initial conditions) but have little effect on the ensemble average statistics. In the context of the 2D+slab model, to see a substantial reduction in the ensemble average diffusion coefficient requires a very weak slab contribution and hence was noticed only recently (Ruffolo et al 2008). Subdiffusion has also been found in computer simulations ( Figure 3(b); see also Ruffolo et al 2008).…”
Section: Dmentioning
confidence: 83%
See 2 more Smart Citations
“…Previous computer simulations have shown that in some cases, corresponding to Regime 3 above, temporary topological trapping and suppressed diffusive escape apply to subsets of field lines (with "conditional statistics" that depend on the initial conditions) but have little effect on the ensemble average statistics. In the context of the 2D+slab model, to see a substantial reduction in the ensemble average diffusion coefficient requires a very weak slab contribution and hence was noticed only recently (Ruffolo et al 2008). Subdiffusion has also been found in computer simulations ( Figure 3(b); see also Ruffolo et al 2008).…”
Section: Dmentioning
confidence: 83%
“…Thus, the random walk of magnetic field lines in space is directly relevant to the transport of such particles perpendicular to the large-scale magnetic field (e.g., Jokipii 1966;Urch 1977;Matthaeus et al 2003;Ruffolo et al 2008). Early descriptions of the field line random walk (FLRW) in magnetic turbulence used a quasilinear theory (Jokipii 1966;Jokipii & Parker 1968), which is now known to apply to fluctuations that vary mainly along a large-scale field, such as parallel-propagating Alfvén waves, or for which the Kubo number (see Kubo 1963) is much less than 1 (if it exists).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these particle orbits one can obtain the diffusion parameters κ ∥ and κ ⊥ . This procedure can be seen as standard approach and it was performed by numerous authors (see, e.g., Michałek & Ostrowski, 1996;Mace et al, 2000;Qin et al, 2002aQin et al, , 2002bPommois et al, 2005;Zimbardo et al, 2006;Pommois et al, 2007;Ruffolo et al, 2008;Tautz, 2010;Qin & Shalchi, 2012;Tautz & Shalchi, 2013). However, one can also be interested in the pitch-angle dependence of the different transport parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Ruffolo et al 2006Ruffolo et al , 2008: (i) early measurements in the solar system revealed a 4:3 ratio of solar wind fluctuation energy in the azimuthal direction relative to the radial and the z directions (Belcher & Davids 1971); (ii) the solar wind near Earth has a two-dimensional (2D) turbulence component that is symmetric with respect to the mean field, while another component has wave vectors along the radial direction. But the mean magnetic field follows a spiral structure, thus breaking the axisymmetry (Saur & Bieber 1999); (iii) nonaxisymmetric fluctuations may be important in enhanced latitudinal transport of cosmic rays at high heliographic latitudes (Jokipii et al 1995;Burger & Hattingh 1998).…”
Section: Introductionmentioning
confidence: 99%